Accounting education in developing countries: can accounting expert systems be an alternative/support solution to instructor-based teaching?. (12th October 2009) - Hammami, Helmi; Fedhila, Hassouna
Accounting teaching in developing countries is facing serious challenges due to the increasing number of students. Accounting expert systems as a teaching method can help manage this flow. The objective of this study was to test the effectiveness of expert systems as a teaching method compared to regular professor-based teaching. Knowledge acquisition was tested over two dimensions: a) declarative knowledge; b) procedural knowledge. Findings show that the expert system teaching method was as effective as the professor-based teaching method in reference to declarative knowledge, but it gave better results for procedural knowledge. We conclude that accounting expert systems can be considered an effective support in making knowledge available to students in developing countries, especially in poor ones.